Nitrifying MBBR Performance Optimization in Temperate Climates Through Understanding Biofilm Morphology and Microbiome - Young, Bradley (Université d'Ottawa / University of Ottawa, 2017)
Nitrification is currently the most common means of ammonia removal from wastewaters in temperate climates. In conventional suspended growth systems operating in northern climate regions, nitrification completely ceases at temperatures below 8°C. This is a considerable concern in passive treatment systems where wastewater temperatures can reach as low as 1°C for extended periods in the winter months. There is evidence biofilm technologies have the ability to nitrify at low temperatures, however, the literature is missing an understanding of low temperature nitrification and the subsequent impacts during seasonal changes. Additionally, there is an urgent need to gain a fundamental knowledge of the interplay between nitrifying performance optimization, biofilm morphology and the microbiome. This research aims to fill these needs using nitrifying moving bed biofilm reactors (MBBRs) at the lab and pilot scale. This research concluded the most important factor determining MBBR carrier selection is a combination of surface area and pore space size. Although high surface area to volume carriers are attractive, the propensity to clog at high loading rates significantly decreases the removal rates. The viability of the biomass and ammonia oxidizing bacterial communities were not significantly changed, indicating the ammonia removal rates were reduced due to loss of surface area in the clogged carriers. Operation at 1°C demonstrated significant rates of nitrification can be attained and stable for extended periods of operation. This study developed the first kinetic curve at 1°C with a maximum removal rate of 0.35 gN/m2·d. The performance of the post carbon removal nitrifying MBBR systems were shown to be enhanced at 1°C by an increase in the viable embedded biomass as well as thicker biofilm. This effectively increased the number of viable cells present during low temperature operation, which partially compensated for the significant decrease in rate of ammonia removal per nitrifying cell. At all studied loading rates at 1°C, the ammonia oxidizing bacteria were primarily in the family Nitrosomonadaceae (greater than 95 percent abundance of AOB population) and the nitrite oxidizing bacteria were primarily the genus Nitrospira (greater than 99 percent abundance of NOB population). Operation at 20°C demonstrated high rates of removal in high loaded condition and robustness in extreme low loaded conditions. In both high loaded and extreme low loaded conditions the viability of the nitrifying biomass was sustained, with the family Nitrosomonadaceae as the primary ammonia oxidizing bacteria and the genus Nitrospira as the primary nitrite oxidizing bacteria. In extreme low loaded conditions and as well during start-up phases there are high prevalence of bacteria not directly related to the nitrification process. Their presence however indicates a dynamic process with changes in microbial composition within the biofilm matrix in response to varying conditions. Change in microbial composition likely helps stabilize and maintain the biofilm matrix enhancing process robustness in the temperate climates. The new knowledge gained in this research optimizes the operation of nitrifying MBBR systems and elucidates the impacts of operational conditions on the biofilm and microbial community of nitrifying MBBR systems to further our understanding of nitrifying attached growth treatment technologies. The results of this study are anticipated to be used to design the first MBBR treatment system for year round ammonia removal in passive treatment systems located in northern climate regions.
Keywords: Nitrification; Biofilm; Microbiome; Low temperature; Cell viability; MBBR